Transforming LaTeX Documents into Interactive Websites (with AI & Make4ht): Generar una Web Interactica con LaTeX (usando Make4ht e IA) - Mora-Flores, Walter (2026)
This document presents a configured template for converting LaTeX documents into interactive web pages using Make4ht. It addresses topics such as Make4ht configuration, the conversion of complex environments into SVG images and, with the assistance of AI, the inclusion of interactive activities using HTML, JavaScript, and CSS. The template also covers the integration of multimedia elements like GeoGebra applets and YouTube videos. This bimodal approach allows for the generation of both PDF and HTML, leveraging the advantages of each format: PDF for formal printing and citation, and HTML for accessibility and interactivity on digital devices.